Atomic-level ablation of Au@Ag NRs using ultrafast laser excitation. Issue 41 (22nd September 2021) - Zhu, Dezhi; Yan, Jianfeng; Xie, Jiawang; He, Guangzhi
Abstract : The atomic structure design of metallic nanomaterials plays a vital role in practical applications. Here, we proposed the atomic-level ablation of Au@Ag NRs using ultrafast laser excitation and revealed the interaction mechanisms. Abstract : Metallic nanorods (NRs) are an important class of materials with widespread applications because of their appealing tunable plasmon resonances, high photothermal conversion efficiency, and chemical stability. It is essential to control the shape and atomic structures of metallic NRs for practical applications. Laser processing of metallic NRs relying on light–matter interactions provides many opportunities. However, the atomic-level fabrication of NRs remains a challenge, and the understanding of laser-induced ablation is still limited. Here, we proposed the atomic-level ablation of Au@Ag NRs using ultrafast laser excitation, which suggests that the near-field effect plays a key role in comparison with thermal evaporation. Through ultrafast laser pulse excitation, abundant atomic steps are fabricated in Au@Ag NRs, which can enhance the surface activity. We suggest that this study highlights the role of the laser near-field effect and also provides a facile strategy to tailor the external shape of metallic NRs at the atomic level, opening a pathway to design metallic NRs for energy and environmental applications.